Quality of care in family planning services in Senegal and their outcomes - Shireen Assaf; Wenjuan Wang; Lindsay Mallick (BMC, 2017)
Abstract Background High quality of care in family planning (FP) services has been found to be associated with increased and continued use of contraceptive methods. The interpersonal skills and technical competence of the provider is one of the main components of quality of care. To study the process component of quality of care, the distribution of the FP counseling topics was examined by client, provider and facility characteristics. To assess the outcomes of quality of care, client satisfaction and their knowledge of their method's protection from STIs were used. This study examined the factors associated with these outcomes with a focus on provider counseling and training. Methods Data from the 2012-2013 Senegal Service Provision Assessment survey was used for the analysis. The survey included a representative sample of the health facilities in Senegal and collects data by observing the clients' FP visits and conducting exit interviews. The main outcomes of interest were provider's counseling in FP, client's satisfaction with FP services and client's knowledge of their method's protection from STIs. Several covariates were used in the analysis which represent client, provider and facility characteristics. Results The level of counseling was inadequate-- very low proportions of providers that performed different types of counseling. Counseling was more likely to be provided to new than returning clients. Approximately 84% of the clients were very satisfied with services but only 58% had correct knowledge of their method's protection from STIs. Clients were significantly less likely to be very satisfied when their providers counseled on side effects and when to return, and counseling provided on method's protection from STIs did not significantly improve knowledge in this area. Clients seen by a provider with FP training had almost twice the odds of having correct knowledge about their method's protection from STIs compared with clients seen by a provider with no recent training. Conclusions The percentage of providers offering FP counseling to their clients was relatively low and was ineffective on the client-focused outcomes. Interventions may be required for more effective counseling methods that are client-centered as well as providing more FP training to providers.